1998
DOI: 10.1002/hep.510270233
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of hepatic acyl-coenzyme A synthetase and microsomal triglyceride transfer protein messenger RNAs in the obese and hypertriglyceridemic rat with visceral fat accumulation

Abstract: The liver plays a central role in lipoprotein metabolism. In particular, very-low density lipoprotein (VLDL) is assembled in the hepatocytes and secreted into the blood circulation. The VLDL is then catabolized to low-density lipoprotein by lipoprotein lipase and hepatic triglyceride lipase. Obese subjects, especially those with visceral fat accumulation, are frequently associated with hyperlipidemia, non-insulin-dependent diabetes mellitus (NIDDM), and hypertension. The mechanism of hyperlipidemia in visceral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 50 publications
0
42
1
2
Order By: Relevance
“…Such differences in the analytical approaches used may explain discrepancies between their results and ours. In viscerally obese rats (OLETF rats) at 6 weeks, before the development of insulin resistance, a significant increase of MTP mRNA *P P value adjusted for age **P P value adjusted for age and visceral adipose tissue (AT) levels was observed whereas apoB mRNA levels were similar to those observed in normal rats (LETO rats) (Kuriyama et al 1998). In viscerally obese men, the À493G>T polymorphism has been associated with CETP gene expression, but the precise mechanism whereby CETP regulates apoB is unclear.…”
Section: Discussionmentioning
confidence: 85%
“…Such differences in the analytical approaches used may explain discrepancies between their results and ours. In viscerally obese rats (OLETF rats) at 6 weeks, before the development of insulin resistance, a significant increase of MTP mRNA *P P value adjusted for age **P P value adjusted for age and visceral adipose tissue (AT) levels was observed whereas apoB mRNA levels were similar to those observed in normal rats (LETO rats) (Kuriyama et al 1998). In viscerally obese men, the À493G>T polymorphism has been associated with CETP gene expression, but the precise mechanism whereby CETP regulates apoB is unclear.…”
Section: Discussionmentioning
confidence: 85%
“…A lipid enrichment of the diet stimulates the hepatic expression of MTP mRNA in hamsters in a dose-dependent manner (37), and the genetically obese OLEFT rat, which has increased fatty acid levels in the portal vein, also displays increased hepatic MTP activity and lipoprotein secretion (38). This has led to the suggestion that prolonged increases in flux of fatty acid to the liver may stimulate MTP expression (38). The present data are in accordance with this idea because an elevation of MTP expression in ob/ob mice occurred in the setting of increased triglyceride clearance from the blood as well as increased triglyceride stores in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Our group reported that FFA enhance mRNA expression of microsomal triglyceride transfer protein in the liver, which suggests that increased FFA influx to the liver from visceral fat may contribute increased very-low-density lipoprotein formation and secretion, and results in hyperlipidemia. 18 In contrast to the observation on FFA metabolism, the fate of glycerol, another metabolite of triglyceride lipolysis, has not been well investigated. …”
Section: Fat Topography Y Matsuzawamentioning
confidence: 99%